2001
DOI: 10.1007/s100380170084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hepatic lipase gene promoter nucleotide variations on serum HDL cholesterol concentration in the general Japanese population

Abstract: Genetic factors may play a major role in determining serum high-density lipoprotein (HDL) cholesterol (HDL-C) levels in the general population. Cholesteryl ester transfer protein (CETP) is a strong genetic factor as a determinant of HDL-C levels in Japanese, whereas hepatic lipase (HL) plays a predominant role in Caucasian populations. We investigated the effects of HL gene promoter polymorphisms on HDL-C levels in a general population of Japanese men (n ϭ 299). An HL promoter polymorphism of Ϫ514C/T explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
7
10
0
Order By: Relevance
“…Subjects 1 and 2 were marked HALP with homozygotes of CETP mutation, but subjects with heterozygotes in this study had various HDL-C levels. Other than CETP, LIPC and LPL are responsible for elevated HDL-C level, and T allele of LIPC gene -514C/T polymorphism and 447X allele of LPL gene S447X polymorphism are well known to both cause 3 mg/dL of elevated HDL-C levels in Japanese (LIPC -514T allele: 75%, LPL 447X allele: 22% in Japanese population) [22,23]. If subjects who have a heterozygote of CETP mutation but rather high levels of HDL-C, further analysis involving endothelial lipase [24] and scavenger receptor class B type I (SR-BI) [25,26] activities is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects 1 and 2 were marked HALP with homozygotes of CETP mutation, but subjects with heterozygotes in this study had various HDL-C levels. Other than CETP, LIPC and LPL are responsible for elevated HDL-C level, and T allele of LIPC gene -514C/T polymorphism and 447X allele of LPL gene S447X polymorphism are well known to both cause 3 mg/dL of elevated HDL-C levels in Japanese (LIPC -514T allele: 75%, LPL 447X allele: 22% in Japanese population) [22,23]. If subjects who have a heterozygote of CETP mutation but rather high levels of HDL-C, further analysis involving endothelial lipase [24] and scavenger receptor class B type I (SR-BI) [25,26] activities is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The reports listed in Tables 2 and 3 examined anywhere from two to 38 individuals homozygous for the splicing defect, and none of these individuals was found to have any CETP activity or protein. The same studies examined two to 279 heterozygotes for CETP activity (14,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In the two largest studies, CETP activity for heterozygotes was 58-68% that of controls, suggesting there might be a slight compensation by the wild-type allele for the loss of the mutant allele, either by alterations in expression or reduced catabolism.…”
Section: Multiple Amino Acid Changes/truncationsmentioning
confidence: 99%
“…We previously reported that this polymorphism had a weak effect on increasing HDL-C levels in the Japanese population 40) but did not have a significant association with coronary artery disease in Japanese FH individuals 41) . There is a study showing that in men with coronary artery disease (CAD), HL activity in PHP was 15 -20% lower in heterozygotes and 30% lower in homozygotes for the -514T allele 42) .…”
Section: Polymorphism Of Hl Genementioning
confidence: 99%